Serial-position effects on a free-recall task in bilinguals. Issue 3 (15th March 2016) - Yoo, Jeewon; Kaushanskaya, Margarita
Abstract : In this study, we examined mechanisms that underlie free-recall performance in bilinguals' first language (L1) and second language (L2) through the prism of serial-position effects. On free-recall tasks, a typical pattern of performance follows a U-shaped serial-position curve, where items from the beginning of the list (the primacy effect) and items from the end of the list (the recency effect) are recalled with higher accuracy than items from the middle of the list. The present study contrasted serial-position effects on the free-recall task in Korean-English bilinguals' L1 vs. L2 and examined the relationship between an independent working memory (WM) measure and serial-position effects in bilinguals' two languages. Results revealed stronger pre-recency (primacy and middle) effects in L1 than in L2, but similar recency effects in the two languages. A close association was observed between WM and recall performance in the pre-recency region in the L1 but not in the L2. Together, these findings suggest that linguistic knowledge constrains free-recall performance in bilinguals, but only in the pre-recency region.